Inventarisasi Tumbuhan Araceae Di Hutan Desa Subah Kecamatan Tayan Hilir Kabupaten Sanggau Kalimantan Barat - Masnur Turnip, Dian Nur Widiyanti, Mukarlina, (Universitas Tanjungpura, 2017)
Araceae is a group of plants founded around the yard of the house and is wildly grown in the forest. Illegal logging and changing land use function impact its living in Subah forest. The purpose of the research was to know types of Araceae plants in the forest of Subah village, Tayan Hilir sub-district. The study was conducted for 3 months from February to April 2017 using cruise method. The results show that there are 8 genera Araceae, namely Alocasia, Amydrium, Anadendrum, Caladium, Epipremnum, Rhaphidophora, Scindapsus and Syngonium.